Case reportA case of a Comél-Netherton syndrome patient treated with UVA1 phototherapy - Osmola-Mańkowska, Agnieszka; Silny, Wojciech; Dańczak-Pazdrowska, Aleksandra; Bowszyc-Dmochowska, Monika; Olek-Hrab, Karolina; Sadowska-Przytocka, Anna; Czarnecka-Operacz, Magdalena (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2011)
Comél-Netherton syndrome is a rare autosomal recessive genodermatosis characterized by a triad of manifestations, such as ichthyosis linearis circumflexa, characteristic hair shaft deformities and atopic diathesis. Conservative treatment consists of emollients, keratolytics and antibiotics. Here we present a case of 16-year-old female patient, hospitalized at the Department of Dermatology of Poznan University of Medical Sciences and diagnosed as Netherton syndrome. The patient was treated with medium doses of UVA1 radiation (40-60 J/cm 2 ) generated by GP-24H (Cosmedico, Germany). The expositions were performed tree times weekly, 20 exposures, up to the total dose of 970 J/cm 2 have been proposed in the treatment. Clinical improvement of both types of skin lesions i.e. ichthyotic and eczematous was observed. But after cessation of phototherapy they gradually relapsed after approximately 4 months. Later as the patient was treated with small doses of systemic corticosteroids without any clinical effect. Thereafter systemic retinoids were introduced but although they caused satisfactory clinical improvement severe hair loss developed leading to the withdrawn of the medication. The above results underlined that due to the complexity of etiopathogenesis as well as clinical diversity treatment of Netherton Syndrome remains to be a great challenge for the physicians.